Palladium-catalyzed [4 + 3] dearomatizing cycloaddition reaction of N-iminoquinolinium ylides. Issue 18 (20th May 2020) - Dai, Wenhao; Li, Chunpu; Liu, Yichu; Han, Xu; Li, Xingjun; Chen, Kaixian; Liu, Hong
Abstract : An efficient approach to obtain saturated seven-membered ring containing three heteroatoms has been developed by using a palladium-catalyzed [4 + 3] dearomatizing cycloaddition. This approach features mild conditions and good functional group tolerance. Abstract : In this study, a palladium-catalyzed [4 + 3] dearomatizing cycloaddition of N -iminoquinolinium ylides has been developed for the construction of saturated seven-membered ring in good yields. This approach features mild reaction conditions and good functional group tolerance. Furthermore, gram-scale preparation and transformation were carried out, which further underscored its synthetic utility and applicability.